Quality of Life Among Women With Breast Cancer - Chouchane, A.; Kacem, I.; Bannour, I.; Kahloul, M.; Maoua, M.; Naija, W.; Mrizak, N. (European psychiatry, 2022)
IntroductionBreast cancer (BC) is the most common cancer in women all over the world. Its physical consequences and psychosocial distress had adverse effect on quality of life (QOL).ObjectivesEvaluate the QOL among women with BC.MethodsDescriptive cross-sectional study of BC patients, carried out during a period of 5 years. Socio-demographic and medical data was collected based on a pre-established synoptic sheet. The European Organization for Research and Treatment Quality of Life Questionnaires (EORTC QLQ-C30) and EORTC QLQ-BR23 were used to assess the QOL.ResultsA total of 100 patients were included. The mean age was 52 ± 8 years. The mean overall health score was 77.5 ± 25.5. The mean scores of physical and emotional functioning were 82 ± 25.1 and 90 ± 19.5 respectively. The QLQ-BR23 objectified a body image score of 63 ± 23.9, an average score for sexual functioning of 87.3 ± 22 with loss of sexual enjoyment in 75% of cases. The increase in mean overall health score and physical functioning was significantly associated with type of treatment (p = 0.01). The mean score of emotional functioning was correlated with the feeling of support (p = 0.04). The increase in the patient’s body image score was significantly associated with age (p <10-3), marital status (p = 0.01) and having had a mastectomy (p <10-3).ConclusionsOur results underline the importance of psychosocial care, which must be an integral part of oncological care in women with BC, in order to improve their quality of life.DisclosureNo significant relationships.